The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4028/www.scientific.net/msf.717-720.347
|View full text |Cite
|
Sign up to set email alerts
|

Deflection of Threading Dislocations with Burgers Vector c/c+a Observed in 4H-SiC PVT–Grown Substrates with Associated Stacking Faults

Abstract: A review is presented of Synchrotron White Beam X-ray Topography (SWBXT) studies of stacking faults observed in PVT-Grown 4H-SiC crystals. A detailed analysis of various interesting phenomena were performed and one such observation is the deflection of threading dislocations with Burgers vector c/c+a onto the basal plane and associated stacking faults. Based on the model involving macrostep overgrowth of surface outcrops of threading dislocations, SWBXT image contrast studies of these stacking faults on differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The reduction of extended defects in the epilayer is a key issue in the field of high quality device fabrication. Epitaxial defects such as pits, 28 carrots, 9,31,32 and stacking faults 16,33 are caused by TSDs in the substrate. In most cases, substrate TSDs are either inherited from the seed crystal, or formed during growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction of extended defects in the epilayer is a key issue in the field of high quality device fabrication. Epitaxial defects such as pits, 28 carrots, 9,31,32 and stacking faults 16,33 are caused by TSDs in the substrate. In most cases, substrate TSDs are either inherited from the seed crystal, or formed during growth.…”
Section: Resultsmentioning
confidence: 99%
“…A 6 inches n-type 4H-SiC substrate with an off-cut angle of 4°f rom [0001] toward the [11][12][13][14][15][16][17][18][19][20] direction was prepared, and labeled as Substrate-A. A SiC epitaxial layer with a thickness of 10 μm on Substrate-A was grown, noted as Epitaxy-B.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies on these various dislocations have been reported by many research groups. Dudley et al reported on the deflection of TSDs/TMDs by the overgrowth of macro-steps to form stacking faults [4][5][6]. Inter-conversion between BPDs and TEDs has also been reported by Wang et al due to the step interaction on the growth interface which results in hopping Frank-Read Sources in 4H-SiC [8].…”
Section: Introductionmentioning
confidence: 91%
“…As a consequence, ultra-high-quality SiC grown crystals can be obtained. Dudley et al pointed out that the interaction of macrostep and threading dislocation was responsible for the conversion of threading dislocation during PVT growth. Yamamoto et al reported that the conversion phenomenon depended on the polarity of the growth surface, Si face and C face. On the Si face, TSD conversion frequently occurred, but no TSD conversion was observed on C face solution growth due to the absence of macrosteps .…”
Section: Introductionmentioning
confidence: 99%